First inter-laboratory comparison of Echinococcus granulosus sensu lato diagnosis in Latin America - María Isabel Jercic; Graciela Santillan; Susana Elola; William Quispe Paredes; Lidia B. Conza Blanco; Noelia Morel; Rodrigo Villegas; Baldomero Molina Flores; Cesar M. Gavidia; Marta Cabrera; Alexandre Guerra dos Santos; Manuel J. Sanchez-Vazquez; et al. (Pan American Health Organization, 2019)
Objective. To compare the performance of polymerase chain reaction (PCR) and enzyme-linked immunosorbent assay (ELISA) tests for diagnosing Echinococcus granulosus in dog feces among national reference laboratories in Argentina, Chile, Peru, and Uruguay. Methods. National laboratories affiliated with the Ministry of Health/Agriculture of each country exchanged panels of 10 positive/negative samples obtained from their regular national surveillance programs in November 2015 - November 2016. All laboratories applied PCR; two also applied ELISA techniques. Sensitivity and specificity were determined for each laboratory and concordance of results among the laboratories was evaluated by Cohen Kappa coefficient. Results. Poor concordance (3 of 10 paired comparisons had values of Kappa > 0.4), low sensitivity and specificity across all laboratories, and poor performance of both techniques in detecting E. granulosus in canine feces was demonstrated in this study. An ex-post comparison of the laboratories' test protocols showed substantial heterogeneity that could partially explain poor concordance of results. Conclusion. The results underscore the heterogeneity of canine echinococcosis diagnosis across the region and indicate possible sources of variability. Efforts to standardize canine echinococcosis testing must be included in the plan of action for the Regional Initiative for the Control of Cystic Echinococcosis. Future comparisons with fecal samples of known parasite load are needed.